Effect of the number of coronavirus disease 2019 (COVID-19) vaccination shots on the occurrence of pneumonia, severe pneumonia, and death in SARS-CoV-2-infected patients - Xin, Shijun; Chen, Wei; Yu, Qilin; Gao, Li; Lu, Genjie (Frontiers in Public Health, 2024)
Coronavirus disease (COVID-19) has posed a significant threat to the lives and health of people worldwide since its onset in 2019. However, the relationship between the number of shots of vaccination and the severity of SARS-CoV-2 infected Chinese patients remain unclear.We retrospectively collected information of 829 patients infected SARS-CoV-2 in Ningbo Medical Center Lihuili Hospital from 2022-12-05 to 2023-03-31, then divided them into four groups based on the severity of pneumonia. Last, we compared the difference of the number of shots of COVID-19 vaccination between the four groups considering potential confounding factors using univariate and multivariate logistic regression.Vaccination with two and three doses were positively associated with low prevalence of pneumonia and severe pneumonia both in crude and optimal models, while only three-doses vaccination was correlated with low prevalence of death in SARS-CoV-2 infected patients. In optimal models, SARS-CoV-2 infected individual with advanced age and males were positively associated with high prevalence of pneumonia, severe pneumonia, and death, and with comorbidities that hypertension (OR=2.532, p<0.001) was positively associated with high prevalence of pneumonia (OR=2.532, p<0.001), and diabetes was positively associated with high prevalence of death (OR=1.856, p=0.011). However, this is cross-sectional study, and the causal relationships need to further studies.One dose of vaccine may not have protective effect against pneumonia, severe pneumonia and death, more than one dose of vaccine was an independent protective factor for pneumonia and severe pneumonia, and three doses of vaccine was an independent protective factor for death.